2021
DOI: 10.1002/vzj2.20131
|View full text |Cite
|
Sign up to set email alerts
|

Recharge site assessment through the integration of surface geophysics and cone penetrometer testing

Abstract: The ability to identify, at potential managed aquifer recharge sites, the presence of connected pathways of hydraulically conductive sediments from the ground surface to the water table could help minimize costs and risks associated with recharge operations. A spatially dense dataset had previously been acquired in an almond [Prunus dulcis (Mill.) D.A. Webb] grove in Tulare, CA, using tTEM, a towed transient electromagnetic (tTEM) geophysical method. In order to interpret reliable information about sediment ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Vertical discretization of the resistivity models begins at ∼1 m at the surface and gradually increases to 6-12 m by the depth of investigation, which was between 50 and 70 m; the depth of investigation is considered to be the depth to which the estimates of electrical resistivity are reliable and depends on the subsurface electrical resistivity. Using measurements of sediment behavior, acquired using cone-penetrometer testing, the resistivity data in the vadose zone from one of the sites were transformed to the fraction of coarse-grain-dominated material, referred to as coarse-dominated material (i.e., material consisting mainly of sands and gravels), by empirically determining a resistivity-to-sediment-type transform (Goebel & Knight, 2021).…”
Section: Core Ideasmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertical discretization of the resistivity models begins at ∼1 m at the surface and gradually increases to 6-12 m by the depth of investigation, which was between 50 and 70 m; the depth of investigation is considered to be the depth to which the estimates of electrical resistivity are reliable and depends on the subsurface electrical resistivity. Using measurements of sediment behavior, acquired using cone-penetrometer testing, the resistivity data in the vadose zone from one of the sites were transformed to the fraction of coarse-grain-dominated material, referred to as coarse-dominated material (i.e., material consisting mainly of sands and gravels), by empirically determining a resistivity-to-sediment-type transform (Goebel & Knight, 2021).…”
Section: Core Ideasmentioning
confidence: 99%
“…The preferential flow path depicted by the dashed white line was manually selected using the spatial distribution of units with a high fraction of coarse-dominated material. Figure modified from Goebel and Knight (2021) In the study by Goebel and Knight (2021), the sparse 3D model displaying the spatial variation in the fraction of coarse-dominated material was qualitatively interpreted to determine where there appeared to be preferential flow paths from the surface to the water table at a site. An example is shown in Figure 1 (modified from Goebel and Knight [2021]), where the authors identified a potential connected pathway of coarse-dominated material through the subsurface.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an alternate way to transform the resistivity model to obtain information about the composition of the subsurface, and that is to capture information about the percentage of each sediment type that is present. Such an approach was recently taken in the interpretation of ground‐based transient EM data (Goebel & Knight, 2021) and is directly applicable to AEM data. In this approach, it is assumed that there is finer‐scale layering of sediment type, below the scale of the AEM resistivity cell.…”
Section: Introductionmentioning
confidence: 99%